2006
DOI: 10.1262/jrd.17073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Experimental Cryptorchidism on Sperm Motility and Testicular Endocrinology in Adult Male Rats

Abstract: Abstract. The effect of induced cryptorchidism on testicular function and sperm motility was investigated. Bilateral cryptorchidism was created surgically in adult male rats (treated group), and sham-operated rats were used as a control group. Five rats from each group were sacrificed on days 1, 3, 5, and 7 after surgery. The percentage of motile spermatozoa began to decrease 1 day after the operation, followed by an abrupt decline 3 and 5 days later in cryptorchid rats. Furthermore, there were significant dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
23
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 54 publications
9
23
0
2
Order By: Relevance
“…In previous studies, it has been reported that as the plasma concentration of testosterone decreases, sperm motility also decreases [9,18]. However, sperm motility does not decrease immediately, but rather decreases gradually along with the concentration of plasma testosterone [26]. In the present study, testosterone-dependent sperm motility parameters significantly decreased in rats fed a PaA-deficient diet as compared with control rats, which is correlated with the lowering of testosterone secretion by PaA deficiency.…”
Section: Discussionsupporting
confidence: 60%
“…In previous studies, it has been reported that as the plasma concentration of testosterone decreases, sperm motility also decreases [9,18]. However, sperm motility does not decrease immediately, but rather decreases gradually along with the concentration of plasma testosterone [26]. In the present study, testosterone-dependent sperm motility parameters significantly decreased in rats fed a PaA-deficient diet as compared with control rats, which is correlated with the lowering of testosterone secretion by PaA deficiency.…”
Section: Discussionsupporting
confidence: 60%
“…The blood plasma INH concentration of cryptorchid men [3,7,21] and experimental cryptorchid rats [27] has been found to be lower than in normal men and rats. The authors have reported lower Sertoli cell function in experimental cryptorchid testes from dogs than in the contralateral scrotal testes [17].…”
Section: Discussionmentioning
confidence: 99%
“…Testis descent was prevented by suturing the inguinal canal. The right testis was kept in the scrotum [21]. The applied procedures were approved by the research ethical committee, Faculty of Medicine, Cairo University.…”
Section: Experimental Designmentioning
confidence: 99%
“…Moreover, this elevated temperature was also shown to cause degenerative changes both in Sertoli and germ cells and has also been associated with decreased sperm motility [21]. In addition, it was shown that Cx lead to AJs disintegration [20].…”
Section: Introductionmentioning
confidence: 99%